2016
DOI: 10.1038/srep37082
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline, metronidazole and isotretinoin: Do they modify microRNA/mRNA expression profiles and function in murine T-cells?

Abstract: 1Inflammatory bowel disease (IBD) may develop due to an inflammatory response to commensal gut microbiota triggered by environmental factors in a genetically susceptible host. Isotretinoin (acne therapy) has been inconsistently associated with IBD onset and flares but prior treatment with antibiotics, also associated with IBD development, complicates the confirmation of this association. Here we studied in mice whether doxycycline, metronidazole or isotretinoin induce epigenetic modifications, and consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 67 publications
1
36
0
1
Order By: Relevance
“…Blocking the interaction between alpha4beta7 and Madcam1 attenuates inflammation in IBD patients [45,46]. In our previous transcriptome study in T cells, we did not observe an increase of those gut-homing markers in CD4+ CD25+ and CD4+ CD62L+ T cells on mRNA level directly after isotretinoin treatment and later on [28]. Interestingly, when analyzing the transcriptome of IECs after isotretinoin treatment, we also did not identify an increase of the aforementioned adhesion markers but an upregulation of tolerance-associated surface integrins, such as ITGAE (CD103) and ITGAX (CD11c) [47,48] on mRNA level in IECs.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Blocking the interaction between alpha4beta7 and Madcam1 attenuates inflammation in IBD patients [45,46]. In our previous transcriptome study in T cells, we did not observe an increase of those gut-homing markers in CD4+ CD25+ and CD4+ CD62L+ T cells on mRNA level directly after isotretinoin treatment and later on [28]. Interestingly, when analyzing the transcriptome of IECs after isotretinoin treatment, we also did not identify an increase of the aforementioned adhesion markers but an upregulation of tolerance-associated surface integrins, such as ITGAE (CD103) and ITGAX (CD11c) [47,48] on mRNA level in IECs.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous studies showed a systemic decrease in serum IL-12p40 levels [20], and no impact on the course of colitis after isotretinoin treatment in DSS-and T-cell-transfer colitis models. Furthermore, isotretinoin induced an anti-inflammatory immune cell profile in vitro and in vivo [21,28]. Pedrotti et al described local intestinal effects on lamina propria cells after systemic changes of IL-12 levels [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations